Engineering Nano-aggregates: β-Cyclodextrin Facilitates the Thiol-Gold Nanoparticle Self-Assembly - D Badmapriya; Sameena Yousuf; Israel Enoch (Journal of Nanostructures, 2019)
The structure and morphology of nonmaterial formed by colloidal synthesis represent a subject of interest as it is a factor deciding the physicochemical properties and biological applications of nanostructures. Among various nanoparticles, gold can develop fractal assembled patterns. Herein, we report a nano-aggregate of a thiol-on-gold self-assembled structure and the influence of β-cyclodextrin on the self-assembly. The host: guest association of the 5-(4-pyridyl)-1,3,4-oxadiazole-2-thiol is studied using UV-visible, fluorescence spectroscopy and molecular modelling analysis. In free form unbound to gold nanoparticles, the thiol compound forms a cyclodextrin complex with a 1: 1 stoichiometry. The thiol assembled on gold nanoparticles, aggregating to constitute irregular patterns. β-cyclodextrin encapsulates the thiol-on-gold nanoparticles and their morphology changes. The influence of β-cyclodextrin on the aggregation of the thiol guest molecule and the morphology of the thiol-on-gold nanostructure is discussed. The non-covalent complex made up by the thiol molecule with cyclodextrin plays a vital role in tuning the structure of the nanostructure when assembled on gold nanoparticles.The study will open up a significant method in the approach towards site specific drug delivery via a physical encapsulation.